Johannes Buridanus: Summulae: De practica sophismatum - Pironet, F. (Brepols, 2004)
The present volume presents a new critical edition of Buridan’s Sophismata based on a collection of six manuscripts and an incunabulum. It forms part of an international project to edit the whole of John Buridan’s Summulae dialecticae, the most extensive version of which consists of nine treatises (tractatus). The treatise on sophisms is the ninth treatise of the Summulae dialecticae and deals with most of the major subjects discussed by the fourteenth century logicians (signification, supposition, appellation, truth-conditions, insolubles, etc.). Although it illustrates how some of the theorems of the preceding treatises may be put to use, it can not be considered a systematic practical companion to the preceding collection of theorems. It is nevertheless one of the most important pieces among Buridan’s works.